The Problem of Being Judged Within a Reasonable Time Under Burundian Law - Ndikumasabo, Noel (European Scientific Journal, ESJ, 2025)
In the course of a trial, both the speed of justice and its slowness present virtues and vices that are sometimes difficult to reconcile. A dialectical conflict arises between modern currents advocating for celerity and traditionalist currents emphasizing the length and quality of trials, grounded in strict respect for the rights of the defense. In either case, the litigant’s interest is not only to obtain a fair legal decision but, above all, to obtain it within a reasonable timeframe, enabling them to fully enjoy the rights enshrined therein. This paper focuses on analyzing how the criteria for assessing reasonable time can help reconcile the demands of the right to defense with those of judicial efficiency_- an issue that often results in delays during case proceedings.. In Burundian positive law, although the Constitution enshrines the principle of the right to be tried within a reasonable time, the notion of reasonable time, as well as its assessment criteria, is not detailed in any legislative or regulatory text, nor is it enshrined in national case law. This gap sometimes leads to unreasonable delays in legal proceedings. Given the advances made by the case law of the Human Rights Committee, the European Court, and the African Court regarding reasonable time, it is more essential than ever for Burundian positive law to foster a "culture of celerity". This would entail accelerating trial proceedings by promoting these criteria for the effective management of judicial time. Furthermore, the article emphasizes the delicate balance between the speed and quality of justice, debunking the common confusion between reasonable time and the hasty administration of justice. Drawing on legal maxims, it argues that while ‘justice delayed is justice denied,’ ‘justice hurried is justice buried.’ The author introduces the idea of reconciling speed with the rights of the defense, demonstrating that expedited justice is beneficial when combined with fundamental defense rights, such as public debates and the principle of contradiction during the trial process. The article asserts that the expeditious delivery of justice, when managed prudently and reinforced by procedural safeguards, is essential for the survival of judicial proceedings. A rule of law system should prioritize efficiency without compromising quality or the rights of the defense. It criticizes unnecessary delays, advocates for practical measures to expedite civil cases, and proposes a streamlined process for legal proceedings. Ultimately, the narrative underscores the need for reasonable judicial time as a cornerstone of a just and fair society. The results of this research are derived from doctrine, the jurisprudence of the Human Rights Committee, case law of the European Court of Human Rights and the African Court of Human and Peoples’ Rights, as well as Burundian case law. The discussion of these results is based on a documentary methodology, analyzing legal texts, books, judgments, and rulings with the force of res judicata, along with national and international case law. This article seeks to examine the challenges and issues associated with the right to be tried within a reasonable time in Burundi. Its objectives is to analyze whether the guarantees proclaimed by the Constitution, the African Charter, and other international instruments ratified by Burundi, specifically those related to reasonable trial time, are effectively being implemented.